2006
DOI: 10.1038/sj.npp.1301009
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Transporter Blockade can Normalize the Prepulse Inhibition Deficits Found in Dopamine Transporter Knockout Mice

Abstract: Dopamine transporter knockout (DAT KO) mice display deficits in sensorimotor gating that are manifested by reduced prepulse inhibition (PPI) of the acoustic startle reflex. Since PPI deficits may model some of the cognitive dysfunctions identified in certain neuropsychiatric patients, we have studied the effects of transporter blockers on PPI in wild-type and DAT KO mice. Treatments with High dose psychostimulants that block DAT as well as the norepinephrine (NET) and serotonin (SERT) transporters (60 mg/kg co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 44 publications
7
52
0
3
Order By: Relevance
“…Moreover, cocaine disrupted PPI in all three lines of WT mice. Our results in mice corroborate the study by Yamashita et al (2006) and extend it with behavioral data suggesting that amphetamine and cocaine exert differential effects in rodents.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, cocaine disrupted PPI in all three lines of WT mice. Our results in mice corroborate the study by Yamashita et al (2006) and extend it with behavioral data suggesting that amphetamine and cocaine exert differential effects in rodents.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, other studies have found that DA transporter KO mice display increased amphetamineinduced conditioned place preference, and cocaine-and amphetamine-stimulated increases in DA in the nucleus accumbens (Carboni et al, 2001;Budygin et al, 2004). Confounding these reports is Yamashita et al (2006), where cocaine actually increased PPI in DA transporter KO mice, presumably through norepinephrine (NE) transporter blockade. Also, Tilley et al (2007) found that DA transporter knockdown mice exhibit increased cocaine-stimulated locomotor activity.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The DAT knockout mice phenotypes resemble amphetamine-like effects, and both hyperlocomotion and PPI deficits can be reversed with either D 1 or D 2 receptor antagonists [376], the atypical antipsychotics clozapine and quetiapine [377], various antidepressant drugs, and monoamine transporter inhibitors [378]. Thus, the DAT knockout mouse may be a useful animal model for predicting the efficacy of novel drugs for disorders such as schizophrenia that are characterized by a dysregulated limbic DA system.…”
Section: Reviewmentioning
confidence: 99%